ASPEK AMAN, IMUN, DAN IMAN PADA PEMBELAJARAN PENDIDIKAN JASMANI DI IAIN SALATIGA SELAMA PANDEMI COVID-19 [THE ASPECTS OF SAFETY, IMMUNITY, AND FAITH IN PHYSICAL EDUCATION LEARNING AT IAIN SALATIGA DURING THE COVID-19 PANDEMIC] - Fatkhur Rozi; Abdul Aziz Purnomo Shidiq; Alvin Yanuar Rahman (Polyglot, 2021)
The focus of this research is on the aspects of safety, immunity, and faith in learning Physical Education (PE) at IAIN Salatiga. This study aims to analyze the aspects of safety, immunity, and faith in physical education learning at IAIN Salatiga. This study uses a qualitative method with a phenomenological approach and uses a case study design. The results of this research show that the safety aspect has been implemented in Physical Education learning at IAIN Salatiga by fully implementing online learning. Furthermore, the immunity aspect is carried out in physical education learning by implementing a physical fitness independent exercise program. Finally, the faith aspect is achieved by praying together before and after Physical Education learning. This research concludes that the aspects of safety, immunity, and faith have been implemented in physical education learning at IAIN Salatiga during the Covid-19 Pandemic.BAHASA INDONESIA ABSTRACT: Fokus penelitian ini tentang aspek aman, imun, dan iman dalam pembelajaran pendidikan jasmani (penjas) di IAIN Salatiga. Penelitian ini bertujuan untuk menganalisis aspek aman, imun, dan iman dalam pembelajaran penjas di IAIN Salatiga. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis dan menggunakan desain case study. Hasil penelitian ini adalah aspek aman telah dilaksanakan dalam pembelajaran penjas di IAIN Salatiga dengan cara melaksanakan pembelajaran penuh dalam jaringan (daring). Selanjutnya, aspek imun dilaksanakan dalam pembelajaran penjas dengan cara pelaksanaan program latihan mandiri kebugaran jasmani. Sementara itu aspek iman dicapai dengan cara melaksanakan do’a bersama sebelum dan sesudah pembelajaran penjas. Simpulan penelitian ini adalah aspek aman, imun, dan iman telah dilaksanakan dalam pembelajaran penjas di IAIN Salatiga selama Pandemi Covid-19.